Characterisation of tennis racket performance in laboratory set-up - Tan, Donovan Qia Zong (2017)
Tennis is a sport where one could easily learn and play with an opponent using a racket and tennis ball. However, do you know that the contact area where the tennis ball hits racket will affect the power of the rebounded ball? This project aims to assist manufacturers to enhance their tennis racket & improve tennis players’ performance. An experiment is conducted to: test out the accuracy of tennis racket sensor which captures the speed of the outbound ball; determine the power point area; locate the impact point where most energy is lost and result in lower speed; calculate a reliable estimation of outbound velocity depending on impact point; and examine the outbound speed depending on the ball contact area. The results show that the sensor has quite a significant margin of error in determining the actual speed of outbound ball. The power point which gives the maximum outbound velocity is located nearest to the throat of the racket. Larger contact area of tennis ball with racket will result in slower outbound velocity. With velocities known from various impact points, the velocities for any other tested impact points on the tennis racket face can be determined.